MOTIVASI WISATAWAN PADA TAMAN NASIONAL TESSO NILO DI KABUPATEN PELALAWAN PROVINSI RIAU - Surahman "; Firdaus Yusrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research aims to find out the motives and motivators that affect tourists visiting the Tesso Nilo National Park Pelalawan district of Riau province.This research uses descriptive quantitative methods to examine the the problems raised. The sample in this study as many as 100 people were taken using accidential sampling. While data collection techniques in this research use observations, questionnaires and interviews. By using a Likert scale as a measure to determine the length of the short interval.Based on this research is the effect of motivating motivator more tourists to visit the Tesso Nilo National Park of motives. And, according to respondents tourist motivation to visit Tesso Nilo National Park enough.Keywords: Motif, Motivator, Travelers, Tesso Nilo National Park